2021
DOI: 10.1175/jcli-d-20-0075.1
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Indian and Pacific Ocean Impacts on the Euro-Atlantic Response to ENSO and Its Transition from Early to Late Winter

Abstract: The present study focuses on the mechanism that controls the transition of the Euro-Atlantic circulation responses to the El Niño-Southern Oscillation (ENSO) from early (December) to late winter (February) for the period 1981-2015. A positive phase of ENSO induces a precipitation dipole with increased precipitation in the western and reduced precipitation in the eastern tropical Indian Ocean; this occurs mainly during early winter (December) and less so in late winter (February). It is shown that these inter-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 53 publications
3
37
1
1
Order By: Relevance
“…In fact, a weak low-level cyclone south of the equator in the western Indian Ocean forms a pair with the cyclone over the North Arabian Sea, Pakistan, and northwestern India (Figure 9d). Since the circulation associated with the IOBW shows a barotropic structure in southwest Asia (Figure 9c,d), our results are consistent with previous findings on the Rossby wave generated by the tropical Indian Ocean warming with an upper-level trough over southwest Asia [57,58]. Our results are also consistent with Liao and Wang [59], who documented a connection between the warming in the tropical Indian Ocean and a warming in the equatorial Atlantic during the austral summer.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, a weak low-level cyclone south of the equator in the western Indian Ocean forms a pair with the cyclone over the North Arabian Sea, Pakistan, and northwestern India (Figure 9d). Since the circulation associated with the IOBW shows a barotropic structure in southwest Asia (Figure 9c,d), our results are consistent with previous findings on the Rossby wave generated by the tropical Indian Ocean warming with an upper-level trough over southwest Asia [57,58]. Our results are also consistent with Liao and Wang [59], who documented a connection between the warming in the tropical Indian Ocean and a warming in the equatorial Atlantic during the austral summer.…”
Section: Discussionsupporting
confidence: 93%
“…To generate the SST pattern, we used a regression of the Niño3.4 time series and HadISST SSTs from 1979-2009. Only pos- King et al, 2018) that may be driven by SSTs and rainfall away from the Pacific (Ayarzagüena et al, 2018;Abid et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…After many decades of research, interest in ENSO teleconnections in the North Atlantic remains high and new results continue to appear (e.g., recent review by Domeisen et al 2018). A number of recent studies have contributed to the continuous improvement in understanding the mechanisms behind the ENSO teleconnection to the North Atlantic, including details about how the late fall signal may arise from an atmospheric bridge via the tropical Atlantic (Ayarzagüena et al 2018;King et al 2018a) or diabatic heating over the Indian Ocean (Abid et al 2020;Joshi et al 2020). Such studies have also found that "free-running" coupled model or SST-forced atmospheric model experiments do not, or only weakly, reproduce the ENSO teleconnection to the North Atlantic through the cold season, while intialized hindcasts perform better.…”
Section: Confidence Intervals and T-testmentioning
confidence: 99%